2014
DOI: 10.1007/s00404-014-3500-5
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative bladder training in patients submitted to radical hysterectomy: is it still necessary? A randomized trial

Abstract: Functional bladder disfunctions are the most common long-term complications following radical hysterectomy. Systematic postoperative bladder training following nerve-sparing radical hysterectomy does not influence the rate of urinary retention or re-admission for bladder catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The length of postoperative IUC placement usually depends on the surgeon's preference and experience, which still remains controversial in scientific field (Fanfani et al . ). Although prolonged bladder drainage has been recommended by some authors, a shorter duration of catheterisation less than seven days could decrease postoperative urinary tract complications such as UTI and bladder retention (Cardosi et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The length of postoperative IUC placement usually depends on the surgeon's preference and experience, which still remains controversial in scientific field (Fanfani et al . ). Although prolonged bladder drainage has been recommended by some authors, a shorter duration of catheterisation less than seven days could decrease postoperative urinary tract complications such as UTI and bladder retention (Cardosi et al .…”
Section: Discussionmentioning
confidence: 97%
“…In a similar study as the present one, Fanfani et al . () evaluated the necessity of bladder training via IUC clamping in patients receiving different types of radical hysterectomy. The authors found the procedure did not influence the rate of urinary retention or bladder recatheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies emphasize that clamping of the urinary catheter can strengthen the detrusor muscle, increase the muscle tone and sensitivity, and return the bladder to its normal function in a shorter time, some other studies put forth that clamping of the urinary catheter had no effect on the development of postoperative urinary retention and re-catheterization. 7,10,11,[20][21][22][23][24][25][26] In our study, the analysis of the incidence rates of residual urine performed in the experimental and control groups at three measurement times demonstrated that there was no significant difference between the groups both on the first day [E: 10 (20%), C: 12 (24%)] and in the first week [E: 2 (4%), C: 3 (6%)]. In the sixth week, no residual urine was observed in any patient in both groups.…”
Section: Discussionmentioning
confidence: 99%
“… 12 14 Sparing nerves and reducing intraoperative hemorrhage 15 , 16 and indwelling urinary catheter for 7–14 days and bladder training are very important in helping patients to restore the bladder voiding function. 17 …”
Section: Discussionmentioning
confidence: 99%